Research and Implementation of Distributed Computing Management System for College Students' Sports Health Based on Integrated Regional Collaborative Medical Care. - Wang, Mian; Li, Lijuan (Occupational Therapy International, 2022)
This paper constructs and applies a university student sports health management system through the theory of integrated regional collaborative medical care and distributed computing technology. Firstly, it analyzes the current situation and problems of cross-regional medical care, the root causes, and the corresponding business scenarios, reflecting the development trend of cross-regional medical care, in the light of the current practical needs of cross-regional medical care. In response to the strong demand for cross-regional medical care, this paper gives the overall design of the distributed computing system, for the deployment and architecture of the cross-regional platform; the registration of cross-regional patients, regional platforms, and health events and documents; and data exchange, service integration, and process integration, etc. The corresponding design is given. The research was conducted on several medical institutions to refine the functional requirements for the construction of the regional collaborative medical platform, and the requirements were analyzed to present the research results of the collaborative medical project. Based on this, requirements were made for the preparation of the project construction data center and medical institutions, and the remote consultation and two-way referral modules of the distributed collaborative medical platform were designed, which are processed and analyzed through a system composed of multiple servers. The results are returned to the user, and the design results were tested for functionality, compatibility, security, and other usability tests. The necessity and feasibility of the college physical health test data platform were analyzed. Students have various needs for physical test data management, the necessity of designing the college physical health test data platform, and the feasibility of the college physical health test data platform in terms of technical means, theoretical basis, and social environment.